Workplace Stress And Burnout Among Paramedics In The Saudi Red Crescent Authority: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Paramedics working in emergency medical services (EMS) operate under unpredictable, high-intensity conditions that expose them to significant psychological strain and elevate the risk of burnout. In Saudi Arabia, the Saudi Red Crescent Authority (SRCA) is the primary provider of prehospital emergency care, yet the extent and determinants of stress and burnout among its paramedics remain insufficiently consolidated.Aim: This systematic review synthesizes empirical evidence on workplace stress and burnout among SRCA paramedics, identifies key contributing factors, and examines associated consequences to guide organizational and policy-level improvements.Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, CINAHL, PsycINFO, and Google Scholar for studies published between 2015 and 2025. Eligible studies focused on SRCA paramedics and assessed stress, burnout, or psychological distress. PRISMA 2020 guidelines were followed for screening, methodological appraisal, and data extraction.Results: Fourteen studies met the inclusion criteria, representing diverse regions of Saudi Arabia. Overall, findings revealed moderate-to-high levels of workplace stress and burnout, with emotional exhaustion consistently emerging as the most affected dimension. Major contributors included high workload, shift rotations, exposure to traumatic events, organizational climate, and limited access to psychological support. COVID-19 further intensified distress, with several studies reporting heightened anxiety, fear of infection, and post-traumatic stress symptoms. Burnout was strongly associated with decreased job satisfaction, impaired performance, medical errors, and higher turnover intentions.Conclusion: Stress and burnout among SRCA paramedics represent a critical workforce and patient-safety challenge. Strengthening organizational support systems, optimizing workload distribution, enhancing access to psychological services, and integrating resilience-building programs are essential for improving staff well-being and service quality. Further longitudinal and intervention-focused studies are needed to guide sustainable mental health strategies within the SRCA.